Analisis Peran Guru dalam Pengembangan Kurikulum di SMP Muhammadiyah Imam Syuhodo Wonorejo, Polokarto, Sukoharjo : Penelitian - Praptiningsih Praptiningsih; Tita Pratiwi; Luthfia Martna Fia; Adefarsa Kaila Azahya; Rizkhi Putri Nur Ikhsani (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Teachers play a central role in curriculum development, determining the direction and quality of education. As the forefront of the learning process, teachers act not only as implementers but also as designers, developers, and evaluators who ensure that the curriculum is effectively applied according to students’ needs. Curriculum development requires teachers to interpret the national curriculum, adapt it to local contexts, and create creative and innovative learning experiences. Teachers are also responsible for instilling moral, spiritual, and character values, ensuring that education shapes holistic personalities rather than focusing solely on cognitive aspects. Moreover, teachers must be adaptive to technological advances and social changes to maintain the relevance of learning in modern times. Collaboration among teachers, school leaders, parents, and the community serves as a vital factor in building a dynamic and responsive curriculum system. Therefore, teachers are considered the primary agents of educational transformation who play a key role in achieving national education goals by fostering students who are faithful, knowledgeable, creative, and virtuous.